Cut price, advertise, or innovate : a study of managerial decision tendencies in increasing market share. - Lee, Shu Fen. (2009)
Price cut, advertising, and product innovation, the three common actions by managers to increase firms’ market shares, have always been focus of many studies. We have observed that out of the three actions, managers are more inclined to carry out price cuts particularly in highly competitive industries, despite research findings pointing to the disadvantages of aggressive price cuts. However, little research has been conducted to examine the relative frequencies of price cuts, advertising and innovation decisions in a single setting. This study aims to bridge the research gap by comparing the occurrences of the three managerial decisions in a standardised, controlled setting.